2021
DOI: 10.1107/s160057672100755x
|View full text |Cite
|
Sign up to set email alerts
|

reciprocalspaceship: a Python library for crystallographic data analysis

Abstract: Crystallography uses the diffraction of X-rays, electrons or neutrons by crystals to provide invaluable data on the atomic structure of matter, from single atoms to ribosomes. Much of crystallography's success is due to the software packages developed to enable automated processing of diffraction data. However, the analysis of unconventional diffraction experiments can still pose significant challenges – many existing programs are closed source, sparsely documented, or challenging to integrate with modern libr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In Xtrapol8, the user has the choice to calculate q -weighted, k -weighted or non-weighted Fourier difference maps, but the default is set to q -weighting. In the k -weighting scheme, the extent to which outliers are downweighed can be adjusted by an additional parameter, that has been set to 0.05 19 or 1.0 8 , 20 depending on reports, with the first one being the default in Xtrapol8.…”
Section: Resultsmentioning
confidence: 99%
“…In Xtrapol8, the user has the choice to calculate q -weighted, k -weighted or non-weighted Fourier difference maps, but the default is set to q -weighting. In the k -weighting scheme, the extent to which outliers are downweighed can be adjusted by an additional parameter, that has been set to 0.05 19 or 1.0 8 , 20 depending on reports, with the first one being the default in Xtrapol8.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the effect of high-redundancy data collection, we scaled and merged each of the four data sets with increasing numbers of consecutive frames in AIMLESS (Evans & Murshudov, 2013). We computed half-data-set correlation coefficients of the anomalous differences (CC anom ) for different numbers of frames using reciprocalspaceship (Greisman et al, 2021) to implement repeated twofold crossvalidation. With this, we determined the mean and standard deviations of the CC anom by resolution bin for the HEWL S-SAD data set.…”
Section: Assessing the Impact Of Redundancy On CC Anommentioning
confidence: 99%
“…Although Dalton et al (2022) demonstrated that Student's t-distribution offers superior performance to a normally distributed error model in some cases, it may not be the optimal choice. For a positively distributed quantity such as intensity, the optimal error model may not be symmetric (see, for example, Greisman et al, 2021). Future work may address this shortcoming by deriving a more appropriate error model.…”
Section: Error Modelsmentioning
confidence: 99%